Equine eosinophilic keratoconjunctivitis in California: retrospective study of 47 eyes from 29 cases (1993‐2017). (31st January 2019) - Knickelbein, Kelly E.; Luethy, Daniela; Thomasy, Sara M.; Reilly, Christopher; Strom, Ann R.; Lassaline, Mary E.
Abstract: Objective: (a) To evaluate the epidemiology of equine eosinophilic keratoconjunctivitis (EK) in the western United States, (b) to ascertain the efficacy of keratectomy and diamond burr debridement vs medical management alone, (c) to determine the efficacy of various medical therapies, and (d) to further characterize the histopathologic findings of the disease in horses. Animals studied: Twenty‐nine horses (47 eyes) diagnosed with EK from 1993 to 2017. Procedure: Retrospective medical record review; owner questionnaire. Results: Average age of presentation was 11 ± 4 years. Warmbloods were significantly overrepresented ( P  =   0.024). Twenty horses were treated with medical therapy alone, five were treated with superficial lamellar keratectomy, and four were treated with diamond burr debridement. Follow‐up data were available for 38 eyes of 23 horses. Median time to resolution for horses treated with either superficial keratectomy or diamond burr debridement (62 days) was not statistically significantly different from those that underwent medical therapy alone (46 days; P  =   0.33). Eyes treated with topical steroids had a statistically significant longer median time to resolution (61 days) compared to those that did not receive topical steroid (44 days; P  =   0.023). Common histopathologic findings in keratectomy samples included the presence of eosinophils, vascularization, and an eosinophilic membrane spanning areas of ulceration. Conclusion: In this population, time to EK resolution was similar for horses treated with medical and surgical management. The use of topical steroids was associated with a prolonged time to resolution. Keratectomy samples from horses with EK had similar findings to those reported in other species.